Educação especial no ensino superior : acessibilidade no processo de inclusão escolar, a partir de relatos de acadêmicos com deficiência - Tavares, Ana Paula da Paz (2014)
The educational services for people with disabilities has been made according to the standards in different historical moments and in different cultures, about the vision of man, evaluation and education. We can say that in many cultures, secreted long these people, since they considered only costly to the nation, and restricted opportunities so they could show their efficient side. There was therefore no possibility of a generalization from the deficiency that presented. Educationally, this also occurred, for these people to education was organized later. This is a very important factor to justify such a small number of people with disabilities attending higher education. This level of education, although few have come, educational alternatives have been addressed in order to provide the same learning opportunities for all people. Are organized in some Universities, strategies to ensure accessibility of entry and stay in academics. Some have completed courses of higher education, and this demand is a reliable source for evaluating the accessibility features that have been provided as well, difficulties, limits and possibilities experienced this level of education. This study, which is an empirical research and is based on the assumptions of Historical Cultural Psychology, objective look at the disabled students , graduates trained at the State University of Maringa in the decade from 2000 to 2010, information on inclusion in higher education , with regard to accessibility, as a condition for the appropriation of scientific subjects at university. For both graduates five students were interviewed with a semistructured script whose guiding referred to schooling, affordability in higher education. The results analyzed in the light of the reference of Historical- Cultural Psychology , revealed that, although they are prescribed in national laws, which express the current National Policies for Education and Higher Education, the educational accessibility, communication and architectural as a condition of ownership of content, is in development and many difficulties for its implementation has been observed, as misinformation from initial teacher training; conceptions of disbelief in learning and development of people with disabilities, individualization of learning disabilities, with justifications in biologizing aspects such as disability, and underlies all these difficulties, the lack of attitudinal accessibility, which could lead to discussions and activities based on an understanding of the historical and cultural contextualization about exclusion as a phenomenon rooted, historically constructed and intensified in capitalist society we live in. The themes analyzed: individualization of learning disabilities, provided ownership of classroom content and recommendations of the university, raise discussions on the difficulties listed, and does not exhaust but can contribute to reflections on the feasibility of accessibility within universities and the starting point for actions whose commitment is, in fact, with the possibility of humanization of all people, including disabled students in higher education.